Fungal Infection and Inflammation in Cystic Fibrosis - T. Spencer Poore; Gina Hong; Edith T. Zemanick (Pathogens, 2021)
Fungi are frequently recovered from lower airway samples from people with cystic fibrosis (CF), yet the role of fungi in the progression of lung disease is debated. Recent studies suggest worsening clinical outcomes associated with airway fungal detection, although most studies to date are retrospective or observational. The presence of fungi can elicit a T helper cell type 2 (Th-2) mediated inflammatory reaction known as allergic bronchopulmonary aspergillosis (ABPA), particularly in those with a genetic atopic predisposition. In this review, we discuss the epidemiology of fungal infections in people with CF, risk factors associated with development of fungal infections, and microbiologic approaches for isolation and identification of fungi. We review the spectrum of fungal disease presentations, clinical outcomes after isolation of fungi from airway samples, and the importance of considering airway co-infections. Finally, we discuss the association between fungi and airway inflammation highlighting gaps in knowledge and future research questions that may further elucidate the role of fungus in lung disease progression.